Molecular level computational studies of polyethylene and polyacrylonitrile composites containing single walled carbon nanotubes: effect of carboxylic acid functionalization on nanotube-polymer interfacial properties - Haghighatpanah, Shayesteh; Bohlén, Martin; Bolton, Kim (Frontiers in Chemistry, 2014)
Molecular dynamics and molecular mechanics methods have been used to investigate additive-polymer interfacial properties in single walled carbon nanotube – polyethylene and single walled carbon nanotube – polyacrylonitrile composites. Properties such as the interfacial shear stress and bonding energy are similar for the two composites. In contrast, functionalizing the single walled carbon nanotubes with carboxylic acid groups leads to an increase in these properties, with a larger increase for the polar polyacrylonitrile composite. Increasing the percentage of carbon atoms that were functionalized from 1% to 5% also leads to an increase in the interfacial properties. In addition, the interfacial properties depend on the location of the functional groups on the single walled carbon nanotube wall.